Mitigation of salt stress in lettuce by a biostimulant that protects the root absorption zone and improves biochemical responses - Zuzunaga-Rosas, Javier; Calone, Roberta; Mircea, Diana M.; Shakya, Rashmi; Ibáñez-Asensio, Sara; Boscaiu, Monica; Fita, Ana; Moreno-Ramón, Héctor; Vicente, Oscar (Frontiers in Plant Science, 2024)
Horticultural crops constantly face abiotic stress factors such as salinity, which have intensified in recent years due to accelerated climate change, significantly affecting their yields and profitability. Under these conditions, it has become necessary to implement effective and sustainable solutions to guarantee agricultural productivity and food security. The influence of BALOX ® , a biostimulant of plant origin, was tested on the responses to salinity of Lactuca sativa L. var. longifolia plants exposed to salt concentrations up to 150 mM NaCl, evaluating different biometric and biochemical properties after 28 days of treatment. Control plants were cultivated under the same conditions but without the biostimulant treatment. An in situ analysis of root characteristics using a non-destructive, real-time method was also performed. The salt stress treatments inhibited plant growth, reduced chlorophyll and carotenoid contents, and increased the concentrations of Na + and Cl -in roots and leaves while reducing those of Ca 2+ . BALOX ® application had a positive effect because it stimulated plant growth and the level of Ca 2+ and photosynthetic pigments. In addition, it reduced the content of Na + and Cl -in the presence and the absence of salt. The biostimulant also reduced the salt-induced accumulation of stress biomarkers, such as proline, malondialdehyde (MDA), and hydrogen peroxide (H2O2). Therefore, BALOX ® appears to significantly reduce osmotic, ionic and oxidative stress levels in salt-treated plants. Furthermore, the analysis of the salt treatments' and the biostimulant's direct effects on roots indicated that BALOX ® 's primary mechanism of action probably involves improving plant nutrition, even under severe salt stress conditions, by protecting and stimulating the root absorption zone.